Sarvepalli Radhakrishnan: a biography of his vision and ideas - Grover, Verinder(ed.) (New Delhi Deep & Deep Publications, 1998)
This book critically analyses the thoughts and ideas of Servepalli Radhakrishnan.
Keywords: President; Biography